Innovation of Sago Into Dry Cakes (DA, DAK) - Miranda, Miranda; Ima, Ima; Insani, Nurul Aulia; Maghfirah, Rabiah; Kasmiati, Kasmiati; Mulia, Nurcahya Indah; Sinta, Sinta; Rajiman, Widyawanti; Sapar, Sapar (PROMOTOR, 2024)
Before rice became widely known in its current form, sago was the staple food of Indonesian people. Sago is eaten in the form of papeda, a type of porridge, or other preparations. Sago is unique as a source of carbohydrates because it is produced in wetlands, a natural habitat for straw. This condition has benefits for the environment but is less economical and more difficult to distribute. Sago is popular among many people in Kitakagiri, and many foods are made from it. Dhadak is a typical food from the Masamba area in Kitakagiri district. Not many people know about this food. However, not many people know about Dhadak, a food made from sago and coconut. Dhadak is a typical Masamba regional dish and is one of the traditional dishes. This product is rarely available on the market and almost non-existent. Apart from being used as food and a complementary ingredient, sago has been proven to provide significant benefits to the ecological chain. Like the sago area, this area is a breeding ground for various types of living creatures, including wild boars, snakes, beetles and birds. Apart from that, from a health perspective, sago is one of the best plants that is able to convert the sun's photosynthetic energy through its leaves and channel it to nature. This means that being around trees can help people avoid lung disease and asthma.